EFEKTIVITAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TERHADAP PERKAWINAN ANAK DI BAWAH UMUR (STUDI KASUS DI DESA MEKARSARI, KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT) - NI LUH GINASTINI; HJ.RINA SUWASTI (GANEC SWARA, 2019)
Marriage is a sacred bond between two people who have committed to foster a sakinah household in the frame of mawaddah and rahmah. In order to achieve these goals, there is a need for maturity of thinking and acting between the two. Therefore, maturity in age becomes important to be prioritized as a measure of one's readiness in uniting the vision of life with his partner.   The purpose of this study is to look at the effectiveness of Law No. 1 of 1974 article 7 paragraph 2 on the implementation of marriage and the efforts of community leaders and KUA officials to improve the effectiveness of underage marriage regulations in Mekarsaari Village, Gunungsari District, West Lombok using Normative Juridical Research Types, approaches through legislation, conceptual, case and sociological approaches   The results showed that, of the population in Mekarsari Village as many as 4652 people consisting of 7 hamlets, there are 362 underage marriages found in Ranjok Barat and Ranjok Timur sub-villages, meaning that in Mekar Sari village the incidence of underage marriages is only 8% of the population. This shows that in Mekarsari Village in implementing regulations in the marriage of minors according to Law No. 1 of 1974 which is very effective because of the efforts made by village staff to regulate the number of underage marriage according to Law No. 1 of 1974 Article 7 paragraph 1 concerning the legality of marriage and the efforts of village community leaders to provide counseling, outreach and approaches to adolescents and rural communities regarding reproductive health and the impact of underage marriages.